2012
DOI: 10.1093/europace/eus052
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-mediated up-regulation of connective tissue growth factor promotes atrial tissue fibrosis in the canine atrial fibrillation model

Abstract: AimsRemodelling of the extracellular matrix (ECM) plays an important role in the production of arrhythmogenic substrate for atrial fibrillation (AF), and is considered to be promoted by the connective tissue growth factor (CTGF). Our objective was to assess the relationship between CTGF and ECM synthesis, and the effect of olmesartan on these processes.Methods and resultsFifteen canine AF models were produced by rapid atrial stimulation. They were divided into three groups: pacing control (n = 5): 6-week pacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
2
29
0
1
Order By: Relevance
“…10 In the last two decades, Ang-(1-7), which is another heptapeptide formed from Ang-I and/or Ang-II, became a novel focus in the RAS because of its protective roles in the cardiovascular system (i.e. vasodilation and antifibrotic effects).…”
Section: Discussionmentioning
confidence: 99%
“…10 In the last two decades, Ang-(1-7), which is another heptapeptide formed from Ang-I and/or Ang-II, became a novel focus in the RAS because of its protective roles in the cardiovascular system (i.e. vasodilation and antifibrotic effects).…”
Section: Discussionmentioning
confidence: 99%
“…30 Similar effects have been observed in a dog model with atrial tachypacing. 31 In addition, in a rat model of OSA, repetitive obstructive respiratory events during 4 weeks resulted in structural atrial remodeling characterized by increased fibrosis formation and cellular hypertrophy. 16,18 Effect of RDN on Atrial Arrhythmias, RAAS Activation, and Atrial Oxidative Stress Previously, we have shown that RDN ameliorated the hypoxia/NTP-induced shortening of atrial effective refractory period and inhibited artificially induced episodes of AF during 1 single obstructive respiratory event.…”
Section: Potential Impact Of Repetitive Obstructive Respiratory Eventmentioning
confidence: 99%
“…30 Similar effects have been observed in a dog model with atrial tachypacing. 31 In addition, in a rat model of OSA, repetitive obstructive respiratory events during 4 weeks resulted in structural atrial remodeling characterized by increased fibrosis formation and cellular hypertrophy. …”
mentioning
confidence: 99%
“…AT1R antagonism appeared to attenuate collagen synthesis, fibrosis and structural remodeling in rabbit model of atrial fibrillation and it was proposed that OLM acted through the inhibition of p38MAPK/ERK pathway in cardiac fibroblasts [14]. Furthermore, in the canine model of atrial fibrillation, interstitial fibrosis was caused by the AT1R-dependent up-regulation of strong mediator of ECM synthesis, CTGF, and this effect was partially abolished by OLM [15].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, OLM administered after a myocardial infarction attenuated injury-evoked up-regulation of BAX protein, Fas receptor and Fas ligand [16]. Similarly, the induction of TNF-a expression in the rat model of steatohepatitis was limited by the inhibition of AT1R signaling by OLM [15]. In a study of experimental autoimmune myocarditis OLM prevented apoptosis by decreasing the levels of mediators of oxidative stress, endoplasmic reticulum stress, and cardiac inflammatory mediators [17].…”
Section: Discussionmentioning
confidence: 99%